Comparison of the pain levels of computer-controlled and conventional anesthesia techniques in prosthodontic treatment - Murat Yenisey (University of São Paulo, 2009)
OBJECTIVE: The objective of this study was to compare the pain levels on opposite sides of the maxilla at needle insertion during delivery of local anesthetic solution and tooth preparation for both conventional and anterior middle superior alveolar (AMSA) technique with the Wand computer-controlled local anesthesia application. MATERIAL AND METHODS: Pain scores of 16 patients were evaluated with a 5-point verbal rating scale (VRS) and data were analyzed nonparametrically. Pain differences at needle insertion, during delivery of local anesthetic, and at tooth preparation, for conventional versus the Wand technique, were analyzed using the Mann-Whitney U test (p=0.01). RESULTS: The Wand technique had a lower pain level compared to conventional injection for needle insertion (p<0.01). In the anesthetic delivery phase, pain level for the Wand technique was lower (p<0.01). However, there was no difference between the Wand and conventional technique for pain level during tooth preparation (p>0.05). CONCLUSIONS: The AMSA technique using the Wand is recommended for prosthodontic treatment because it reduces pain during needle insertion and during delivery of local anaesthetic. However, these two techniques have the same pain levels for tooth preparation.